LIVING QUR'AN PERSPEKTIF PENDIDIKAN ISLAM: BELAJAR DARI TRADISI KEAGAMAAN ETNIS SASAK TRANSMIGRASI DI DESA KARYA MUKTI DONGGALA SULAWESI TENGAH - Baitur Rahman; Saed M Adam; Hasanah Hasanah; Moh. Ilham (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
This study examines the Living Qur’an in the religious traditions of the Sasak ethnic group in Karya Mukti Village, Dampelas District, Donggala Regency, from the perspective of Islamic education. The main focus of this research is to explore how the implementation of the Living Qur’an within the religious traditions of the Sasak community in Karya Mukti Village can be viewed from an educational perspective, particularly in shaping Islamic character through Qur’anic values. This study employs a qualitative method with a descriptive approach. Data were collected through interviews with village heads, religious leaders, traditional leaders, and community figures, as well as through relevant documentation. The data collection techniques included observation, interviews, and document analysis. The data were analyzed through reduction, presentation, and conclusion drawing. The findings indicate that the implementation of the Living Qur’an is reflected in various religious practices such as completing the Qur’an, congregational prayers, serakan, and hiziban, all of which embody Qur’anic values. Furthermore, Islamic values are manifested in the community’s social life through attitudes of tolerance, cooperation, and respect for religious leaders. From the perspective of Islamic education, these traditions play a significant role in the informal transmission of Islamic values that shape the religious and social character of the younger generation. Thus, the Living Qur'an serves not only as a spiritual symbol but also as a contextual educational medium rooted in local culture.